In silico investigation of Alliin as potential activator for AMPA receptor. (10th November 2021) - Ozturk, Hilal; Yorulmaz, Nuri; Durgun, Mustafa; Basoglu, Harun
Abstract: Natural products from plants, such as flavonoids, arouse immense interest in medicine because of the therapeutic and many other bioactive properties. The molecular docking is a very useful method to screen the molecules based on their free binding energies and give important structural suggestions about how molecules might activate or inhibit the target receptor by comparing reference molecules. Alliin and Allicin differ from many other flavonoids because of containing no benzene rings and having nitrogen and sulfur atoms in their structure. In this study Alliin and Allicin affinity on AMPA, NMDA and GABA-A receptors were evaluated in the central nervous system by using the molecular docking method. Both Alliin and Allicin indicated no inhibitory effects. However Alliin showed significant selectivity to human AMPA receptor (3RN8) as an excitatory. The binding energy of glutamate to 3RN8 was −6.61 kcal mol −1, while the binding energy of Allin was −8.08 kcal mol −1 . Furthermore Alliin's affinity to the other AMPA and NMDA receptors is quite satisfactory compared to the reference molecule glutamate. In conclusion based on the molecular docking study, Alliin can be useful for synaptic plasticity studies whereas might be enhance seizure activity because of the increased permeability to cations. It also can be beneficial to improve learning and memory and can be used as a supportive product to the hypofunction of NMDA associated problems.